Komunikasi Interpersonal Tenaga Kerja Indonesia dan Anak - Rehia Karenina Isabella Barus; Salamiah Sari Dewi; Khairuddin Khairuddin (Mahesa Research Center, 2020)
This study focuses on the Interpersonal Communication of Children of Indonesian Workers with Their Parents. This study is motivated by the reality of communication problems experienced by children whose parents work as Indonesian workers abroad. The relationship between children and parents is then bridged by the presence of communication technology media such as cellular phones and social media. The purpose of this study was to determine 1) Barriers to interpersonal communication between children and parents; 2) Form of parental attention to children; 3) Interpersonal Communication Process of Children and Parents. This study uses the findings of this study to indicate that First: The weakness of interpersonal communication between children and their parents is due to communication technology connections that are often cut off as well as their parents' busyness so that the network can communicate with children. Another obstacle is the lack of interpersonal meaning due to gestures and expressions that are not recognized because of indirect communication; Second: Parents pay attention to the condition of the child, but not in detail so that violations are often committed by children; Third: The form of the message in the form of closed questions causes a lack of feedback which reduces the dynamics of the conversation between parents and children.